EKSISTENSI HUKUM ADAT DALAM PENYELESAIAN KONFLIK PADA DAERAH OTONOM - Warjiyati, Sri (Ahkam: Jurnal Hukum Islam, 2018)
In addition to the current positive law or written law or product legislation there is also an unwritten law which is a living law. The law which grows, develops, and is maintained in a society is better known as Customary law. Customary law as a law born from the personality of the Indonesian nation is clearly very important for the Indonesian people. Customary law is an expression or statement of human thoughts and feelings about the just and unjust growing in society. Until now the Indonesian people in autonomous regions tend to respect the customary laws that apply in their area, for example are the nagari law in Minangkabau, the nagari law in Aceh, the Fondrako law (customary law and customary procedures) in the Nias Islands North Sumatra. Local people choose not to violate the customary law because of severe sanctions and are reluctant to the deal with traditional institutions or communities so that customary law is respected by people in autonomous regions like this. Other problems that often arise in the community, usually, are related to land disputes, inheritance, etc., for example the land dispute that occurred in 2017 in the Segene Balik village, KutePanang Subdistrict, Central Aceh, which was able to be resolved by the customary justice. This shows how the existence of customary law in resolving conflicts in autonomous regions currently has a very important role. Given that it is not always written law in the form of legislation, the customary law can always follow the development of the society. Another important role, customary law as a law that lives, grows and develops in the community, is the main source of the formulation of legislation.Keywords: Existence of Customary Law, Autonomous Region, Conflict